2012
DOI: 10.1111/j.1447-0594.2012.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of chrysin against oxidative stress in d‐galactose‐induced aging in an experimental rat model

Abstract: These results suggest that chrysin protects against oxidative stress-induced tissue damage in D-galactose-induced aging in an experimental rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 49 publications
4
57
0
Order By: Relevance
“…SOD, the main endogenous antioxidant enzyme, could protect tissues against the harmfulness of free radicals [31,32]. GSH-Px activity is a major mechanism for intracellular decomposition of lipid peroxidase [33]. MDA could reflect the status of oxidative stress [34].…”
Section: Discussionmentioning
confidence: 99%
“…SOD, the main endogenous antioxidant enzyme, could protect tissues against the harmfulness of free radicals [31,32]. GSH-Px activity is a major mechanism for intracellular decomposition of lipid peroxidase [33]. MDA could reflect the status of oxidative stress [34].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these investigations yielded promising results. For example, Uhl et al [13] demonstrated antimutagenic properties against benzo(a)pyrene B(a)P induced DNA-damage in HepG2 cells and Salmonella typhimurium ; Anand et al [14] showed that CR reduces the disturbances of redox status, named superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione (GSH) in liver, kidney, and brain tissues of rats treated with D-galactose.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic administration of D -galactose ( D -gal) which induces neurotoxicity is a common model used to study aging and memory impairment [1,2,3,4,5]. There are 3 main aspects of the mechanism of D -gal-induced aging.…”
Section: Introductionmentioning
confidence: 99%